Wendy helps out - Inches, Alison (New York : Simon Spotlight, 2001)
When Bob the builder is too sick to work, his assistant Wendy helps the trucks fix the road for him.
Accelerated Reader AR
Keywords: Bob the Builder (Fictitious character) -- Juvenile fiction; Trucks -- Fiction; Roads -- Maintenance and repair -- Fiction; Friendship -- Fiction; Sick -- Fiction